Menstrual health and hygiene management among female college students and their mothers in Thoothukudi district, Tamil Nadu, India - Devi, Indra; George, Sobha (International Journal Of Community Medicine And Public Health, 2023)
Background: A two-generation study on menstrual health and hygiene practices among daughters and their mothers is limited. In this study, the primary objective was to compare menstrual health practices, period poverty and menstrual hygiene practices between female college students and their mothers. Methods: A community-based cross-sectional study was conducted among 500 female college students (mean age 19 years) and their mothers (n=500, mean age 41 years) in the Thoothukudi district. Five colleges were selected from the twenty colleges in the district using simple random sampling. From the list of students from the selected colleges, female students were selected using computer-generated random numbers and the mothers of all the selected students were included in the study. Information on menstrual health, period poverty and menstrual hygiene was collected using a pre-tested structured interview schedule. Results: Among daughters, 80.4% speak about menstrual pain more than mothers 44% (p<0.001). Of the daughters, 46.2% and 19.8% of the mothers had information about menstruation before menarche (p<0.001). Among daughters 63% and among mothers 30.2% are embarrassed about buying period products (p<0.001). Sanitary pad use among daughters was 93.2% compared to 69.9% among mothers (p=0.001). Using cloth as their menstrual product was reported by 21.8% of daughters and 50.4% of mothers (p=0.001). Conclusions: During menstruation, daughters reported better hygiene practices than their mothers. However, some of the daughters still use clothes as menstrual material, which needs improvement.